Digital response to safety in educational institutions in Ibadan Metropolis, Oyo State, Nigeria - Akinyooye , Funmilola Elizabeth (American Journal of Education and Learning, 2025)
The use of advanced technologies in digital safety responses aims to prevent, manage, and react to safety incidents in real-time. Nevertheless, educational institutions in developing regions frequently face issues such as violence, bullying, and emergencies, which ultimately jeopardize the safety of both students and staff. Consequently, this research investigated the role of digital safety measures in educational institutions located in Ibadan Metropolis, Oyo State, Nigeria, by identifying existing digital technologies, assessing the level of awareness and usage, and recognizing barriers to implementation. The research utilized a descriptive research design, focusing on the entire population of educational institutions within Ibadan Metropolis, Oyo State, Nigeria. A total of two hundred participants were purposively selected, and a self-constructed questionnaire was employed to gather data from the sampled respondents. The findings showed that digital safety tools, including metal detectors for entry, panic buttons, access control systems, fire alarm systems, and others, were not only sufficiently present but also had low levels of awareness and utilization in educational institutions in the Ibadan Metropolis. The findings additionally highlighted that factors such as limited ICT (Information Communication Technology) knowledge, low internet bandwidth, lack of access to ICT, inadequate ICT skills, high costs of technology, lack of training facilities, absence of technical resources, and insufficient infrastructure were significant obstacles to the availability and utilization of digital safety tools in educational institutions within the studied area. The study concluded that the availability of digital safety gadgets in educational institutions is a necessary condition for their awareness and usage.